2003
DOI: 10.1021/tx025685q
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Acetate Causes DNA Single Strand Breaks In Vitro in the Presence of Ascorbate (Vitamin C)

Abstract: Uranium is a radioactive heavy metal with isotopes that decay on the geological time scale. People are exposed to uranium through uranium mining, processing, the resulting mine tailings, and the use of depleted uranium in the military. Acute exposures to uranium are chemically toxic to the kidney; however, little is known about chronic exposures, for example, if there is a direct chemical genotoxicity of uranium. The hypothesis that is being tested in the current work is that hexavalent uranium, as uranyl ion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 19 publications
(25 reference statements)
4
87
0
Order By: Relevance
“…Among experiments focused on uranium toxicity evaluation, Yazzie et al [3] also demonstrated uranium-induced genotoxicity (via an in vitro experiment carried out on plasmid DNA). Theses authors hypothesized that hexavalent uranium, as uranyl ion, may have a chemical genotoxicity similar to that of hexavalent chromium (a known human carcinogen), since there are some parallels between their chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among experiments focused on uranium toxicity evaluation, Yazzie et al [3] also demonstrated uranium-induced genotoxicity (via an in vitro experiment carried out on plasmid DNA). Theses authors hypothesized that hexavalent uranium, as uranyl ion, may have a chemical genotoxicity similar to that of hexavalent chromium (a known human carcinogen), since there are some parallels between their chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, uranium is categorized as a heavy metal with a radiotoxic potential, it is the heaviest naturally occurring element and its typical concentration range in surface waters is 3.10 -2 to 2 µg/L [1]. Considering uranium chemical characteristics, as any heavy metal, this radioelement is a potent genotoxic compound via the formation of oxidative DNA damages due to the redox chemistry of transition metals and their ability to activate oxygen species in the course of redox reactions [2] [3]. In the same way, its radiological properties being characterized by ionising radiations (mainly via the emission of α particles) can enhance this free radical production [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been found that people subjected to heavy amounts of stress are more susceptible to uranium toxicity (Albina et al 2003). Previous studies have shown cancer mortality in men living in counties of Colorado where uranium tailings were used as construction fills (Yazzie et al 2003). It is further demonstrated that uranium can be correlated with their mutagenicity in a dose and time dependent manner (Stearns et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to uranium often occurs during mining, processing, and from mine tailings (Yazzie et al 2003). Therefore, effective management of waste uranium compounds is necessary to prevent exposure and adverse health effects cause a growing concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation